Peran dan Tanggung Jawab Konsumen Untuk Mencegah Praktik Penipuan dalam Transaksi Online dari Perspektif Hukum Perlindungan Konsumen - Zayyan Qurrotul A’ini (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
The aim of this research is to analyze the role of consumers in preventing fraud in online transactions and to explore the rights and responsibilities of consumers in protecting themselves from such fraud. The method used in this study is literature review and legal analysis related to consumer protection in Indonesia, particularly in the context of online transactions. The discussion in this research includes the importance of verifying information, being cautious of too-good-to-be-true offers, understanding electronic contracts, and the legal protection provided to consumers based on applicable regulations. This research also discusses the responsibilities of consumers in protecting themselves from fraud and the steps they can take to report fraud to the relevant authorities. The conclusion of this study emphasizes the crucial role of active consumers in maintaining the security and integrity of online transactions, as well as the need to raise awareness and understanding of consumer protection.